The Effect of Financial Ratios on Stock Prices- An Econometric Study Using Factor Analysis - bouledjenib, adel (Journal of Research in Finance and Accounting, 2022)
This study aims to examine the impact of financial ratios on the stock prices. For this purpose, the study used eighteen financial ratios, classified into five main categories, the first express the extent to which the firm can generate profits from sales, the second express the efficiency of using the firm’s assets to generate revenues and profits, the third express what a single share obtains as a result of the firm’s activity or liquidation, the fourth measure the profitability and the risk of shareholders' capital, and the fifth show the firm's ability to pay its short-term debts. This classification was done by using a factor analysis model. Based on a multiple regression model, the research concluded that the first, second, third and fifth categories have a significant relationship with the change in stock prices, while the fourth category does not affect stock prices.